Identification of a de novo mutation of the FOXG1 gene and comprehensive analysis for molecular factors in Chinese FOXG1-related encephalopathies - Lu, Guanting; Zhang, Yan; Xia, Huiyun; He, Xiaoyan; Xu, Pei; Wu, Lianying; Li, Ding; Ma, Liya; Wu, Jin; Peng, Qiongling (Frontiers in Molecular Neuroscience, 2022)
FOXG1-related encephalopathy, also known as FOXG1 syndrome or FOXG1-related disorder, affects most aspects of development and causes microcephaly and brain malformations. This syndrome was previously considered to be the congenital variant of Rett syndrome. The abnormal function or expression of FOXG1, caused by intragenic mutations, microdeletions or microduplications, was considered to be crucial pathological factor for this disorder. Currently, most of the FOXG1-related encephalopathies have been identified in Europeans and North Americans, and relatively few Chinese cases were reported. A de novo nonsense mutation (c.385G>T, p.Glu129Ter) of FOXG1 was identified in a female child in a cohort of 73 Chinese children with neurodevelopmental disorders/intellectual disorders (NDDs/IDs). In order to have a comprehensive view of FOXG1-related encephalopathy in China, relevant published reports were browsed and twelve cases with mutations in FOXG1 or copy number variants (CNVs) involving FOXG1 gene were involved in the analysis eventually. Feeding difficulties, seizures, delayed speech, corpus callosum hypoplasia and underdevelopment of frontal and temporal lobes occurred in almost all cases. Out of the 12 cases, eight patients (66.67%) had single-nucleotide mutations of FOXG1 gene and four patients (33.33%) had CNVs involving FOXG1 (3 microdeletions and 1 microduplication). The expression of FOXG1 could also be potentially disturbed by deletions of several brain-active regulatory elements located in intergenic FOXG1-PRKD1 region. Further analysis indicated that PRKD1 might be a cooperating factor to regulate the expression of FOXG1, MECP2 and CDKL5 to contribute the RTT/RTT-like disorders. This re-analysis would broaden the existed knowledge about the molecular etiology and be helpful for diagnosis, treatment, and gene therapy of FOXG1-related disorders in the future.